2020
DOI: 10.1242/jcs.246199
|View full text |Cite
|
Sign up to set email alerts
|

Integration of JAK/STAT receptor-ligand trafficking, signalling and gene expression in Drosophila melanogaster cells

Abstract: The JAK/STAT pathway is an essential signalling cascade required for multiple processes during development and for adult homeostasis. A key question in understanding this pathway is how it is regulated in different cell contexts. Here we have examined how endocytic processing contributes to signalling by the single cytokine receptor, Domeless, in Drosophila melanogaster cells. We identify an evolutionarily conserved di-Leu motif that is required for Domeless internalisation and show that endocytosis is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 79 publications
(107 reference statements)
3
12
0
Order By: Relevance
“…Previous studies have shown that blocking trafficking in distinct endosomal compartments leads to an inhibition of the JAK/STAT pathway, 56 and the internalization and endocytic trafficking of activated Dome allows for compartmentalized signalling to regulate subsets of Drosophila JAK/STAT transcriptional targets. 57 These results strongly supports that the internalization and trafficking are both required for JAK/STAT activity. Therefore, endocytosis may also affect the EGFR signalling pathway through indirect means.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have shown that blocking trafficking in distinct endosomal compartments leads to an inhibition of the JAK/STAT pathway, 56 and the internalization and endocytic trafficking of activated Dome allows for compartmentalized signalling to regulate subsets of Drosophila JAK/STAT transcriptional targets. 57 These results strongly supports that the internalization and trafficking are both required for JAK/STAT activity. Therefore, endocytosis may also affect the EGFR signalling pathway through indirect means.…”
Section: Discussionsupporting
confidence: 60%
“…The essential role of CME in JAK/STAT signaling was further confirmed a year later in Drosophila with the receptor Domeless (Dome) whose internalization is also required to transduce JAK/STAT signaling, (105). Like IFNAR1 and IFNAR2, Dome presents fibronectin type-III extracellular domains (106) and a conserved di-leucine motif in its cytosolic tail (107). These data emphasize that the control of JAK/STAT signaling by receptor endocytosis is a conserved mechanism among species.…”
Section: Type I Interferon Receptor Endocytosis Is Mandatory For Jak/stat Signalingmentioning
confidence: 85%
“…Many viruses are known to hijack endocytic mechanisms for entry to the cell (Robinson et al, 2018). However, an antiviral role could be the result of two scenarios: trafficking viral proteins to the lysosome for degradation (Park and Guo, 2014), or regulation of signalling pathways following activation by endocytosis of cytokine receptors (Moore et al, 2020; Zanin et al, 2020).…”
Section: Resultsmentioning
confidence: 99%